If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -1(3n + -1) = 4 + -4n Reorder the terms: 7 + -1(-1 + 3n) = 4 + -4n 7 + (-1 * -1 + 3n * -1) = 4 + -4n 7 + (1 + -3n) = 4 + -4n Combine like terms: 7 + 1 = 8 8 + -3n = 4 + -4n Solving 8 + -3n = 4 + -4n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '4n' to each side of the equation. 8 + -3n + 4n = 4 + -4n + 4n Combine like terms: -3n + 4n = 1n 8 + 1n = 4 + -4n + 4n Combine like terms: -4n + 4n = 0 8 + 1n = 4 + 0 8 + 1n = 4 Add '-8' to each side of the equation. 8 + -8 + 1n = 4 + -8 Combine like terms: 8 + -8 = 0 0 + 1n = 4 + -8 1n = 4 + -8 Combine like terms: 4 + -8 = -4 1n = -4 Divide each side by '1'. n = -4 Simplifying n = -4
| 7/12-8/3x-5/83/8 | | 60=3x-3 | | +(-2)+5-(-2)= | | 3(3n-5)=(7n+5)+1 | | 5-3(t+3)=-1+2(t-3) | | 48=16(d+5) | | 1/7w-3/2=-7/5 | | 0.22y-0.6=0.12y+0.7y | | 2p-22=18+7p | | -2x-11=6x+21 | | 9x-27=4-8x | | 20=y-10 | | 23r=-161 | | 6x-19=-61 | | 2x+2x-4+4x=76 | | -2-(-15)= | | -7t^2-3t+7=0 | | 2(ax+b)+3=x | | -5j^2+2j+5=0 | | 10-1x=20+5x | | 13x+5=50 | | 6y^2-7=0 | | y=-4(x-3) | | y=-4x(x-3)(x+2)(2x-1) | | 5s^2-7=0 | | -5d^2-7d-2=0 | | -2w^2+7w-1=0 | | A=3.14(10) | | -1000/8= | | (-10)(-10)(-10)= | | A=3.14(10)2 | | 3x+10=2x-50 |